2015
DOI: 10.1016/j.sbspro.2015.04.243
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Levels of Use of Basic Process Skills of High School Students

Abstract: It aims to determine the abilities of use of basic process skills of the students and the levels of conceptual learning of the students as oriented to general chemistry topics. The sampling comprises 160 students whose were studying at 10 th and 11 th grades of seven different high schools in Turkey. The study design is based on Survey model. The questionnaire prepared by considering the levels of conceptualization of chemistry topics of the students aims to measure their ability of use of science process skil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 14 publications
2
25
0
6
Order By: Relevance
“…The science process skills are generic skills needed by a scientist to research and study phenomena, solve problems, and make a new invention. The science process skills have an important role in the knowledge acquisition [10]. In this study, we also found the science process skills are also related to the experimental skills and the critical thinking skills.…”
Section: The Impact Of Experimental Skills Using Discoverysupporting
confidence: 62%
“…The science process skills are generic skills needed by a scientist to research and study phenomena, solve problems, and make a new invention. The science process skills have an important role in the knowledge acquisition [10]. In this study, we also found the science process skills are also related to the experimental skills and the critical thinking skills.…”
Section: The Impact Of Experimental Skills Using Discoverysupporting
confidence: 62%
“…Keterlibatan peserta didik yang aktif dalam kegiatan praktikum dapat meningkatkan KPS. Peserta didik dengan KPS yang tinggi dapat memahami permasalahan dan memecahkan masalah secara kompleks [18] . Berdasarkan penelitian yang dilakukan oleh Gurses (2014) di Ataturk University, Turkey menunjukkan bahwa model pembelajaran IT adalah salah satu model yang tepat agar peserta didik memiliki KPS yang tinggi.…”
Section: Hasil Dan Diskusiunclassified
“…Hal ini disebabkan karena model pembelajaran IT dapat membuat peserta didik memiliki keinginan belajar yang baik sehingga aktif dalam belajar dan memiliki rasa tanggung jawab [18] .…”
Section: Hasil Dan Diskusiunclassified
“…It is also known as procedural, experimental, scientific inquiry and thinking skills, which might be drilled through laboratory activities [2], [9], [10]. Basic science process skills (BSPS) were usually experienced in primary school levels and the integrated science process skills (ISPS) can be accomplished by higher level school students [11]. ISPS is the development of basic SPS [8], [12].…”
Section: Introductionmentioning
confidence: 99%